The Review of Clinical Use of Current Anti- VEGF Injections in Retinopathy of Prematurity - (:unkn) unknown (My University, 2015)
Prematüre retinopatisi (PR), gelişmiş ve gelişmekte olan ülkelerdeki çocukluk çağı görme kayıplarının en önde gelen sebeplerindendir. Uygun tarama ve tedavi yöntemleri sayesinde PR'ne bağlı körlük artık belirgin şekilde azalmıştır. Ülkemizdeki yenidoğan yoğun bakım ünitelerinin koşullarında belirginleşmeye başlayan iyileşme, PR insidansında bir artışı da beraberinde getirmiştir. Retinanın geleneksel laserle ablasyonu oldukça etkili olsa da posterior PR, küçük pupil veya retinanın herhangi bir sebeple görülemediği bazı durumlarda uygulanamamaktadır. Ayrıca, periferik retinanın laserle fotoablasyonu anormal damarlanma yanında normal damar gelişimini da kesintiye uğratmaktadır. Son yıllarda, ciddi posterior PR'de intravitreal anti-VEGF (vasküler endotel büyüme faktörü) uygulaması artan şekilde popülarite kazanmıştır. Bu makale, PR tedavisinde güncel anti-VEGF uygulamalarının etkinliğini derlemiştir

ABTRACT Retinopathy of prematurity (ROP) is one of the major causes of visual loss in childhood in developed and developing countries. With the convenient screening and treatment methods, blindness due to ROP has significantly reduced. In Turkey, the incidence of ROP has been gradually increasing upon improved conditions of neonatal intensive care units. Conventional laser retinal photoablation therapy has provided effective results though it is inadequate in certain cases such as posterior ROP, small pupil and hazy ocular media. Additionally, laser photocoagulation destructs peripheral re- tina stopping the physiologic extension of normal blood vessels as well as abnormal ones. The intravitreal administration of anti-VEGF (vascular endothelial growth factor) injection is becoming more popular in the treatment of severe posterior ROP in the last few years. This article reviews the effectiveness of anti-VEGF applications in the treatment of ROP
Prematüre Retinopatisinde Güncel Anti-VEGF Enjeksiyonu Klinik Uygulamalarının Gözden Geçirilmesi
Keywords: Göz Hastalıkları